Research of accelerated depreciation role in the stimulation of innovative development of the enterprise - Трачова, Дар`я Миколаївна (Technology audit and production reserves, 2016)
The modern state of depreciation policy formation of the company is investigated in the article. The problems of inconsistencies of regulations that regulate the formation of depreciation policy of the company are identified. The necessity to add an innovative component in the renewal process of fixed assets is revealed. The study found a positive experience around the world in the use of accelerated depreciation to encourage innovation renovations of assets in various industries. Given the prospects of Ukraine’s accession to the European community, the practice of accelerated depreciation in the countries-members of the European Union is investigated. The recommendations on the feasibility of using accelerated depreciation methods for domestic enterprises are proposed. They are allowed them to be competitive in terms of a common economic space. However, the approach to the process of depreciation policy formation should be comprehensive and include elements of the relevant state regulation. In carrying out reform it is necessary to organize operational monitoring of the results by the state for quickly response to potential problems.